3D hybrid scaffold with aligned nanofiber yarns embedded in injectable hydrogels for monitoring and repairing chronic wounds. (1st April 2022) - Qiu, Weiwang; Wang, Qian; Li, Mengna; Li, Na; Wang, Xueli; Yu, Jianyong; Li, Faxue; Wu, Dequn
Abstract: Pressure ulcers (PU) as a major clinical concern are disproportionately affecting the older adult population and resulting in a lot of medical expenses. The issues of preventing the incidence of PU and treating chronic wounds are urgent to be solved at the present stage. Here, a 3D hybrid scaffold with conductive and antibacterial properties is designed to monitor and repair chronic wounds. The 3D hybrid scaffold is prepared by encapsulating nanofiber yarns (NFY) network into the injectable hydrogel which is cross-linked by Schiff base. The aligned NFY networks assembled by weaving nanofiber yarns consisting of polyacrylonitrile (PAN) and reduced graphene oxide (rGO) can induce cellular elongation and alignment on their 3D peripheral surface. The injectable hydrogels outside not only provide the protection for the cells on the surfaces of the NFYs, but also mimic a native extracellular matrix (ECM) to supply a much more suitable 3D microenvironment for the cells proliferation and arrangement. The addition of ions within the hydrogel endows the hydrogels with excellent conductivity, making the hydrogels the potential flexible strain sensor to exactly monitor the wound pressure. The 3D hybrid scaffold with aligned nanofiber yarns embedded in injectable hydrogels displays favorable biocompatibility, self-healing and antibacterial properties, showing promising medical applications especially in tissue engineering and wearable electronics. Graphical abstract: Image 1